2018
DOI: 10.1177/2329496518804553
|View full text |Cite
|
Sign up to set email alerts
|

Race and Social Boundaries: How Multiracial Identification Matters for Intimate Relationships

Abstract: While researchers have explored in detail how multiracial identification shapes symbolic boundaries (conceptual distinctions), they have paid less attention to its effects on social boundaries (how people behave). This study examines multiracial individuals’ odds of marriage and cohabitation with blacks and whites to examine whether this population challenges current race-based social boundaries via partner choice. Analyses of data from the 2008–2012 American Community Survey (ACS) show that while those who id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In the U.S., there is a clear social consensus that the categories of "Asian," "Black," "Native American," and "White" are distinct "racial" groups. The increasing number of young people who identify as multiracial (U.S. Census 2021; Parker et al 2015) complicates and adds nuance to this simplified categorization process and may lead to more complexity and variation in the process of identity development and in the way that people conceive of "racial" boundary-crossing (Bratter 2007;Buggs 2019;Littlejohn 2019). Moreover, in the U.S., the Hispanic category is treated variously as an ethnic designation that is distinct from one's racial background (e.g., one might identify as Hispanic White and Hispanic Black) and as a racialized category unto itself (e.g., one might identify as Hispanic or non-Hispanic White) (Perlmann and Waters 2002;Parker et al 2015).…”
Section: The Difficulties Of Conceptualizing and Measuring Ir/ie Rela...mentioning
confidence: 99%
“…In the U.S., there is a clear social consensus that the categories of "Asian," "Black," "Native American," and "White" are distinct "racial" groups. The increasing number of young people who identify as multiracial (U.S. Census 2021; Parker et al 2015) complicates and adds nuance to this simplified categorization process and may lead to more complexity and variation in the process of identity development and in the way that people conceive of "racial" boundary-crossing (Bratter 2007;Buggs 2019;Littlejohn 2019). Moreover, in the U.S., the Hispanic category is treated variously as an ethnic designation that is distinct from one's racial background (e.g., one might identify as Hispanic White and Hispanic Black) and as a racialized category unto itself (e.g., one might identify as Hispanic or non-Hispanic White) (Perlmann and Waters 2002;Parker et al 2015).…”
Section: The Difficulties Of Conceptualizing and Measuring Ir/ie Rela...mentioning
confidence: 99%
“…Still other research finds that part‐White multiracials have a greater likelihood of marrying White partners (Littlejohn, ; Miyawaki, ) and question if this indicates cultural group “dilution” for future generations (Song & Gutierrez, ). Yet, debates of the merits and drawbacks of interraciality foreground the mainstream U.S. notion that increased intimacy between people of different races will reduce social inequality despite the fact that scholars have illustrated how interracial relationships in and of themselves are not inherently progressive (Nemoto, ; Steinbugler, ; Twine, ) or that interracial and interethnic couplings may be at greater risk for divorce (Bratter & King, ; Zhang & Van Hook, ), likely tied to the pressures of social inequality.…”
Section: Interracial Relationships and Studying Racial Boundariesmentioning
confidence: 99%
“…It is for these broader reasons that research into online dating has continued to draw interest, as technology plays a significant role in how new relationships are formed and how boundary crossing occurs (Lewis, ; Rosenfeld & Thomas, ). Although there is a wealth of research on interracial couplings inclusive of online dating phenomena, the inclusion of multiracial people in contemporary dating analyses is much more limited (Bonam & Shih, ; Curington et al, ; Littlejohn, ; McGrath et al, ; Miyawaki, ; Qian & Lichter, ) and the qualitative assessments of these dynamics even more so (Buggs, ; Song, , ). These studies come to some similar conclusions regarding the desirability of some multiracial people: Being mixed with White has been found to increase the likelihood of response online (Curington et al, ), and being a non‐Black biracial dater has been found to be consistent with a preference for White partners (Littlejohn, ; McGrath et al, ).…”
Section: Interracial Relationships and Studying Racial Boundariesmentioning
confidence: 99%
See 2 more Smart Citations